Master track of MARIA S. MERIAN cruise MSM140 in 1 sec resolution (zipped, 128 MB) - Ingo Klaucke (PANGAEA, 2025)
Raw data acquired by position sensors on board RV MERIAN during expedition MSM140 were processed to receive a validated master track which can be used as reference of further expedition data. During MSM140 the motion reference unit Kongsberg SeaTex AS MRU-5 combined with Kongsberg SeaTex AS Seapath 320 and the GPS receivers Trimble SPS855 and SAAB R4 were used as navigation sensors. Data were downloaded from DAVIS SHIP data base (http://dship.bsh.de) with a resolution of 1 sec. Processing and evaluation of the data is outlined in the data processing report. Processed data are provided as a master track with 1 sec resolution derived from the position sensors extquotesingle data selected by priority and a generalized track with a reduced set of the most significant positions of the master track.